Changes in social behavior with MAPK2 and KCTD13/CUL3 pathways alterations in two new outbred rat models for the 16p11.2 syndromes with autism spectrum disorders - Martin Lorenzo, Sandra; Muniz Moreno, Maria del Mar; Atas, Helin; Pellen, Marion; Nalesso, Valérie; Raffelsberger, Wolfgang; Prevost, Geraldine; Lindner, Loic; Birling, Marie-Christine; Menoret, Séverine; Tesson, Laurent; Negroni, Luc; et al. (Frontiers in Neuroscience, 2023)
Copy number variations (CNVs) of the human 16p11.2 locus are associated with several developmental/neurocognitive syndromes. Particularly, deletion and duplication of this genetic interval are found in patients with autism spectrum disorders, intellectual disability and other psychiatric traits. The high gene density associated with the region and the strong phenotypic variability of incomplete penetrance, make the study of the 16p11.2 syndromes extremely complex. To systematically study the effect of 16p11.2 CNVs and identify candidate genes and molecular mechanisms involved in the pathophysiology, mouse models were generated previously and showed learning and memory, and to some extent social deficits. To go further in understanding the social deficits caused by 16p11.2 syndromes, we engineered deletion and duplication of the homologous region to the human 16p11.2 genetic interval in two rat outbred strains, Sprague Dawley (SD) and Long Evans (LE). The 16p11.2 rat models displayed convergent defects in social behaviour and in the novel object test in male carriers from both genetic backgrounds. Interestingly major pathways affecting MAPK1 and CUL3 were found altered in the rat 16p11.2 models with additional changes in males compared to females. Altogether, the consequences of the 16p11.2 genetic region dosage on social behaviour are now found in three different species: humans, mice and rats. In addition, the rat models pointed to sexual dimorphism with lower severity of phenotypes in rat females compared to male mutants. This phenomenon is also observed in humans. We are convinced that the two rat models will be key to further investigating social behaviour and understanding the brain mechanisms and specific brain regions that are key to controlling social behaviour.